Impact of Covid-19 on the Inflation Rate of Central Kalimantan Province - Hadifa, Rizki; Hukom, Alexandra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to see the impact of the COVID-19 pandemic on the inflation rate in Province Central Kalimantan. This research uses descriptive quantitative research. The inflation data for Province Central Kalimantan were taken from BPS (Central Statistics Agency) for 2019 - 2020. Data analysis used paired sample t-test. The results of the data normality test used the Kolmogorov-Smirnov p>a = 0.200, so the data were normally distributed. For the analysis of these data, the Paired Samples T Test method is available in the SPSS statistical version 25 software.The results of the paired samples t-test analysis show a significant (2-tailed) value of 0.323 with a significant value <0.05. Research shows the effect of inflation in Central Kalimantan Province by comparing with the year before the COVID-19 pandemic event is insignificant. This means that the impact of the COVID-19 pandemic on inflation is not influential.